16 Long term effects of dispatcher-assisted CPR – did we touch the ceiling?. (26th April 2019) - Franěk, O; Pekara, J; Sukupova, P; Pohlova, M
Abstract : Background: Dispatcher-assisted CPR (D-CPR) is recognized to be an important part of the 'chain of survival' in case of pre-EMS-arrival out-of-hospital cardiac arrest (OHCA). In Prague, D-CPR was introduced in 2003 and since 2006 it should be provided in a routine manner for all calls suspected from OHCA. The aim of the study is to compare the influence of D-CPR to bystander CPR (B-CPR) rates for confirmed OHCA cases in different phases of D-CPR implementation. Method: This is a retrospective analysis of B-CPR rates from Prague Utstein-style OHCA registry after 5, 10 and 15 years of implementation of D-CPR, as compared to the 'baseline' in 2003. Results: Rates of B-CPR in 2003, 2008, 2013 and 2018 were 13.6%, 69.2%, 81.6% and 81.0% respectively. There was a highly significant difference between 2003 and 2008 rates (p<0, 0001), as well as between 2008 and 2013 rates (p<0, 01), but there is no difference between 2013 and 2018 rates (n/s). Conclusion: Full implementation of D-CPR in Prague took more than 5 years. The implementation was associated with very significant increase of B-CPR ratio, which reached as much as 80% in the second period (5–10 years after start of the implementation). Nevertheless, after reaching this level, the L-CPR ratio now remains stable for several years and it seems this method reached its maximum. To increase B-CPR rates significantly over 80% we probably need some new approaches. Conflict of interest: None. Funding: None.